Laser-induced breakdown spectroscopy application for heavy metals detection in water: A review - Goncharova, Iryna; Guichaoua, Dominique; Taboukhat, Said; Tarbi, Amal; Chtouki, Tarek; Erguig, Hassane; Sahraoui, Bouchta (Spectrochimica acta. Part B: Atomic spectroscopy, 2024)
Water quality monitoring is an important part of environmental protection, and the ability to qualitatively and quantitatively determine the level of impurities in water is especially important. Laser-induced breakdown spectroscopy (LIBS) has become a promising technique compared with the currently available water quality control methods. LIBS has several advantages, including minimal or no sample pre-treatment, fast and easy operation, and a chemical-free process. This article reviews the studies conducted on LIBS analysis for the detection of heavy metals in water samples. The article describes a historical perspective at the progress of LIBS, the LIBS instrumentation, LIBS procedures without pre-treatment and different pre-treatment methods of aqueous samples for improving the limit of detection (LOD), quantitative analysis of metallic elements in liquids, LIBS signal enhancement methods and data processing, characteristics of plasma generated by laser in water, improving the LIBS sensitivity for the detection of trace heavy metals in aqueous solutions, factors affecting the accuracy of the analysis results, and LIBS spectra after measurements. This review will help readers better understand the LIBS technique for detecting heavy metals in liquids and identify current research requirements for environmental water quality monitoring. [Display omitted] •LIBS analysis of heavy metals in water is presented.•Pre-treatment methods for LIBS signal improvement are characterised.•LIBS enhancement techniques for increasing limits of detection are discussed.•Factors affecting LIBS in aqueous samples are considered.•LIBS spectra after measurements are analysed.